Spatio-Temporal Analysis of Land Use Land Cover Dynamics, a case study of Iwo Local Government, Nigeria - Abdulwakeel, Saheed Adebayo; Mamboleo, Martin (Journal of Sustainability Perspectives, 2025)
The application of land use land cover change analysis in assessment and monitoring of ecosystem resources ensures informed decision regarding environmental and biodiversity protection. This study investigates the Iwo land use land cover to detect and ascertain the extent of the change for environmental management and policy, and to discern an understanding to relationship between population growth and land use change. Landsat data was collected from United States Geological Survey (USGS) data repository website and processed using ArcGIS 10.7 software. For further analysis, excel analytical tool was also used to reveal pattern of change in the data. The results showed that there has been significant increase in the built-up area at the expense of loss of vegetation and water body land cover. The study highlights rapid urban growth and human activities, leading to ecosystem changes and potential impacts on biodiversity, carbon emissions, and local climate. It is concluded that the rapid changes in land use land cover of Iwo LG needs to be urgently addressed. The study recommends urban forest initiatives and enforcement of environmental laws as urgent actions to address the disappearance of vegetation and water bodies.